Aid, Knowledge, and Power: The Legacy of Imported Expertise at the National College of Arts, Lahore - Sarah K. Cheema (ABE Journal, 2023)
My research aims at identifying and understanding the complicated and often contradictory process(es) of Pakistan’s decolonization in connection with the imported frameworks of knowledge in the structure and pedagogy of the National College of Arts (NCA), Lahore during the formative years of the institution. With a focus on the college’s Architecture Department, the paper begins in 1958 by highlighting the historical context and factual history of the effort to restructure the former colonial craft school. The college’s modernization process is seen to be dictated by the incoming foreign aid and expertise, aligned with the national policies of the new military regime of General Ayub Khan. Thus, the major themes of the paper converge on the Decade of Global Development, the foreign-funded knowledge economy, and its consequent import of expertise at the National College of Arts. Subsequently, the research engages critically with the legacy of this expertise by dissecting the multi-layered process(es) of decolonization. These processes range from questioning the methodologies of modernization and spatial decolonization, questions of gender, and the inclusion of diverse voices in the effort to find alternate knowledge paradigms.